Fiscal transfers for biodiversity conservation: The Portuguese Local Finances Law - Rui Santos; Irene Ring; Paula Antunes; Pedro Clemente (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
Biodiversity loss is a serious global environmental problem. Economic instruments in biodiversity policies can contribute towards reconciling the conservation costs encountered at local level with the benefits of biodiversity conservation at higher levels of governance, from regional and national levels up to the global level. This paper outlines the theoretical foundations of fiscal transfers in conservation policies and also offers a concise account of existing international experience and future prospects. The recently amended Portuguese Local Finances Law (LFL) of 2007, with its groundbreaking new article on the promotion of local sustainability, is analysed in terms of the significance of fiscal transfers for municipal budgets. It is compared with its predecessor law, highlighting changes in fiscal revenues for selected municipalities in the country in relation to their designated protected areas. The anagical fiscal transfers can be significant for those municipalities with a large proportion of land under protected status. However, because it also introduces a considerable number of changes to the Portuguese fiscal transfer scheme, the ecological impact of the new LFL is difficult to assess due to the presence of several crossover effects. The results obtained offer significant insights both for improving the Portuguese LFL and for designing new ecological fiscal transfer schemes.
Keywords: 330; Biodiversity conservation; Protected areas; Natura 2000; Intergovernmental fiscal transfers; Local Finances Law; Portugal; Finanzausgleich; Biodiversität; Gemeindefinanzen; Naturschutz; Portugal